PENGARUH MODEL GAME BASED LEARNING BERBANTUAN MEDIA KARTU PERCAKAPAN TERHADAP PENGUASAAN KOSAKATA BAHASA INGGRIS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Tarigan, Are Benata; Destini, Frida; Abung, Miranda; Khairani, Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem of this research was the low english vocabulary mastery of fourthgrade students of SD Negeri 2 Gondangrejo. This research aimed to determine the effect of the game-based learning model, assisted by conversation card media, on the english vocabulary mastery of fourth-grade students at SD Negeri 2 Gondangrejo. This research used a quantitative approach with an experimental method and a nonequivalent control group design. The population of this research was all fourth-grade students of SD Negeri 2 Gondangrejo, totaling 40 students. The sampling technique used was saturated sampling because the population was small; therefore, the entire population served as the sample, with 20 students from class IV A as the control class and 20 students from class IV B as the experimental class. The data collection techniques used were tests in the form of multiple-choice questions and non-tests in the form of documentation and observation. The data were tested by hypothesis testing using a simple linear regression. The results showed that there was an effect of using the game-based learning model assisted by conversation card media on students' english vocabulary mastery by 42%.